Probability in petroleum and environmental engineering - Khilyuk, Leonid F. (Gulf Pub. Co., 2005)
Written by three of the world's most renowned petroleum and environmental engineers, Probability in Petroleum and Environmental Engineering is the first book to offer the practicing engineer and engineering student new cutting-edge techniques for prediction and forecasting in petroleum engineering and environmental management. The authors combine a rigorous, yet easy-to-understand, approach to probability and how it is applied to petroleum and environmental engineering to solve multiple problems that engineers or geologists face every day.
Keywords: Petroleum engineering -- Statistical methods.; Environmental engineering -- Statistical methods.; Probabilities.; Reliability (Engineering) -- Statistical methods.; elektronické knihy; electronic books